PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP - Sari, Putri Mayang (Departemen Matematika, 2023)
The success of students in learning mathematics can be seen from the results obtained after participating in learning activities. Results of learning mathematics eighth grade students of SMP Negeri 24 Padang still low, because they are less active in learning. Solutions to cope this problem is using the STAD model. The purpose of this study is to analyze and compare the mathematics learning outcomes of students who use models STAD learning and those using the direct learning model, as well as describing the development of mathematics learning outcomes of student who used the STAD learning model. This Quasi-experiment used the Nonequivalent Posttest Only Control Group Design. The results of data analysis with the t test, obtained ? −value < 0.05, indicating that the mathematics learning outcomes of students who use the STAD learning model are better than the direct learning model. Based on value increase quizzes and analysis of final test data, it was concluded that the STAD learning model positive effect on students' mathematics learning outcomes.Keywords– Student Team Achievement Division, Direct Learning, Mathematics Learning Outcomes.